1992
DOI: 10.1172/jci116002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of experimental hyperglycemia on microvascular blood perfusion of pancreatic islet isografts.

Abstract: The influence of hyperglycemia on the microvascular blood perfusion of pancreatic islet isografts of Syrian golden hamsters was analyzed by direct visualization ofthe islet's microvasculature by means of in vivo fluorescence microscopy. The experiments were performed using the hamster dorsal skinfold preparation, which allows for quantitative analysis of the microcirculation of islets grafted on the striated skin muscle. Islets were isolated from inbred hamsters by collagenase digestion and subsequently transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 27 publications
4
57
0
Order By: Relevance
“…1A). In malignant tissue, these vessels even when fully developed have a high heterogeneity in terms of vessel caliber (Vajkoczy et al 1999), while in benign tissue microvessels reveal a progressive decrease in diameter (Menger et al 1992), similar to that observed in the present study.…”
Section: Follicular Angiogenesissupporting
confidence: 88%
“…1A). In malignant tissue, these vessels even when fully developed have a high heterogeneity in terms of vessel caliber (Vajkoczy et al 1999), while in benign tissue microvessels reveal a progressive decrease in diameter (Menger et al 1992), similar to that observed in the present study.…”
Section: Follicular Angiogenesissupporting
confidence: 88%
“…At day 28, the diameter was 8.11 ± 0.53 μm (n = 5, Fig. 2c), which is similar to the intra-islet vasculature in the pancreas 3 and other transplantation sites 17 .…”
Section: Noninvasive Imaging Of Pancreatic Islet Vascularizationsupporting
confidence: 60%
“…2B), as previously documented from dissected pancreatic tissue in vitro (13,14). The increase in intra-islet vessel diameter could be part of a compensatory mechanism designed to increase blood perfusion under hyperglycemic conditions (15). It also might be an approach to optimizing endocrine signaling, ensuring that each beta cell will have direct communication with blood flow under this strong proliferative condition.…”
Section: Intraocular Islet Transplants Mirror the Adaptive Morphologicalmentioning
confidence: 73%